Study on Kinetics of GB and GD hydrolysis by Peroxides with a way of fluoride ion-selective electrode. Issue 1 (1st August 2022) - Xu, Mengxue; Wang, Lianyuan; Zhu, Haiyan; Zhang, Hongpeng; Zhou, Chaohua; Miao, Ting
Abstract: Fluoride ion-selective electrode was widely used in trace F- test of food, medicinal materials and various water sources, etc.. It could also be used to monitor the concentration change of F- produced by GB and GD (G agents) hydrolysis. In this paper, two sorts of peroxide solutions, 1% sodium percarbonate (SPC) and 1 % sodium percarbonate combined with 0.9 % acetylsalicylic acid solution (SPC-Aspirin), worked as decontamination solutions (decon solutions). In view of the effect of ionic strength of decon solution on F- activity, calibration for linear correlation between the concentrations of standard F- aqueous in decon solutions and its related values showeded on the meter with a fluoride ion-selective electrode was firstly done, kinetic experiments of GB and GD hydrolysis were carried subsequently. Results showed that the components of HOO- in SPC and CH3COOO- in SPC-Aspirin played the major role in catalyzing G agents hydrolysis. The stronger nucleophilicity of decon solution was, the faster G agents hydrolyzed. The first order rate constants of GB and GD hydrolysis in SPC-Aspirin solution were 6.8×10-2 s-1 and 5.8×10-2 s-1, respectively, both above 10 times greater than that in SPC solution. Consequently, the nucleophilicity of CH3COOO- was stronger than HOO-. Due to relatively higher stereo-hindrance effect of GD with pinacolyl group, GD hydrolyzed more slowly than GB.